THE ATTEMPT TO FILL UP LA TABLADA (1989). REPRESSION, JUSTICE AND HUMAN RIGHTS - Scocco, Marianela (Revista de Historia Social y de las Mentalidades, 2020)
On January 23, 1989, militants of the MTP group headed by Enrique Gorriarán Merlo –historical leader of the PRT-ERP–, attempted to cover the barracks of the Mechanized Infantry Regiment 3 “General Belgrano” in the Argentine town of La Tablada, with the alleged purpose of thwarting a military coup against the government of Raúl Alfonsín, who had faced three military uprisings throughout his administration. The repression was excessive and violent and left several people injured, dead and disappeared. In this article I intend to analyze the readings of the attack on La Tablada and the course of justice in this regard, emphasizing the violations of human rights produced, the role of the State, the consequences in the modification of repressive laws and change in the correlation of forces in the governments / military relationship.
Keywords: Taking; Military Uprisings; Repression; Justice; Human Rights